PEMULIHAN KUALITAS AIR SUNGAI CILIWUNG MENGGUNAKAN MODEL KUALITAS AIR - Iskandar A. Yusuf (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
In Ciliwung River, pollutant sources coming from domestic waste, breeding, and industry with totalwaste load of about 212 ton BOD/day and estimated in the year 2020 will reach 280 ton BOD/day. Whereas,discharge in Katulampa weir of 10.24 m3/s and 195 m3/s as minimum and maximum discharge respectively,indicate that Ciliwung water quality is very heavily polluted especially in the dry season after passing BogorMunicipality until Jakarta Bay. The water quality modeling applied a finite segment method calibrated withspatial variation at one time by using real time sampling water quality data in order to obtain accurateresults of model calibration. Recovery strategies for the existing very heavily polluted water quality shallapply a water quality target program that has to be completed by the end of the year 2020. Study resultsrecommend a recovery applying a short-term program up to the year 2012 as preparation stage forrestructuring water quality and reviewing the waste load permit. Whereas, the mid-term program shall putinto effect the waste water permit for domestic and industry activities, and wastewater treatment plantperformance auditing. The long-term program shall concentrate on hazardous waste disposal andapplication of clean industrial technology.